2012
DOI: 10.1177/1352458512471094
|View full text |Cite
|
Sign up to set email alerts
|

Month of birth as a latitude-dependent risk factor for multiple sclerosis in Norway

Abstract: This study confirms previous reports of increased MS births in spring and decreased MS births in the winter months. This could support the role of decreased sunlight exposure during pregnancy and vitamin D deficiency in prenatal life in MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 35 publications
2
38
0
Order By: Relevance
“…Studies on season of birth in the Northern hemisphere have frequently reported an increased risk of MS in patients born in spring and summer and a decrease in MS births in autumn and winter months [14][15][16][17][18][19]. A pooled analysis in the largest study, based on datasets from Canada, Great Britain, Denmark and Sweden (n = 42,045) showed an excess of MS among people born in May and a relative deficit among those born in November [20].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on season of birth in the Northern hemisphere have frequently reported an increased risk of MS in patients born in spring and summer and a decrease in MS births in autumn and winter months [14][15][16][17][18][19]. A pooled analysis in the largest study, based on datasets from Canada, Great Britain, Denmark and Sweden (n = 42,045) showed an excess of MS among people born in May and a relative deficit among those born in November [20].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the incidence of developing MS correlates with the risk in areas of childhood residence [4] . Additionally, studies have shown risk association during months of birth as spring births have higher risk of MS than autumn births [17] . Several environmental factors have been investigated.…”
Section: Environmental Factorsmentioning
confidence: 99%
“…The month of birth effect on multiple sclerosis (MS) risk reported by numerous groups,13 has been interpreted as evidence of environmental exposures during the prenatal period influencing the future risk of MS. A recent publication by Fiddes et al 4. suggests that these results rather reflect the failure of adjusting for confounding factors that likely varied according to the areas and cohorts included in these studies.…”
Section: Introductionmentioning
confidence: 99%
“…The authors pointed out that no earlier studies had adequately controlled for confounding factors, and they presented analyses showing that adequately adjusting for year and place of birth would reduce confounding and most likely eliminate the month of birth effect 4. We have previously reported a month of birth effect for MS in Norway 3. The results were adjusted for year, but not place of birth.…”
Section: Introductionmentioning
confidence: 99%